Base de datos de intensidades sísmicas para Colombia y el occidente de Venezuela - Prieto Salazar, Jorge Alonso; Ventura, Carlos E.; Finn, W. D. Liam; Ramos, Alfonso Mariano; Prada-Sarmiento, Luis Felipe (Puerto Rico, 2012)
Este artículo presenta una base de datos de intensidades sísmicas recopiladas para Colombia y el Occidente de Venezuela. Esta base de datos macrosísmica está basada en la recopilación y análisis de información contenida en mapas de isosistas generada por diferentes investigadores en el Norte de Suramérica. La base de datos incluye 68 eventos sísmicos ocurridos entre 1766 y 2004. Para estos eventos, se presentan 283 pares de datos de intensidad – radio equivalente. El presente trabajo constituye la base para futuras investigaciones cuyo objetivo sea mejorar el entendimiento de la atenuación de la energía sísmica en la región.

This article presents an extensive database of seismic intensities compiled for Colombia and Western Venezuela. This macroseismal database is based upon the compilation and analysis of information contained in isoseismal maps produced mainly by researchers in Colombia and Venezuela. The database includes 68 earthquake events, which happened between 1766 and 2004. For these events 283 pairs of Modified Mercalli intensity points and the radii of equivalent isoseismals are presented. This work constitutes the basis for future investigations aimed at improving the understanding of the attenuation of seismic energy in the region. It is considered that the database presented may play a central role in future studies of hazard based on intensity.
Database of Seismic Intensities for Colombia and Western Venezuela
Keywords: Intensidades sísmicas; Isosistas; Sismicidad histórica; Historic seismicity; Isoseismals; Seismic intensities